Melanoma‐associated GRM3 variants dysregulate melanosome trafficking and cAMP signaling. (23rd October 2017) - Neto, Ana; Ceol, Craig J.
Summary: Large‐scale sequencing studies have revealed several genes that are recurrently mutated in melanomas. To annotate the melanoma genome, we have expressed tumor‐associated variants of these genes in zebrafish and characterized their effects on melanocyte development and function. Here, we describe expression of tumor‐associated variants of the recurrently mutated metabotropic glutamate receptor 3 ( GRM3 ) gene. Unlike wild‐type GRM3, tumor‐associated GRM3 variants disrupted trafficking of melanosomes, causing their aggregation in the cell body. Melanosomes are trafficked in a cAMP‐dependent manner, and drugs that directly or indirectly increased cAMP levels were able to suppress melanosome aggregation in mutant GRM3 ‐expressing melanocytes. Our data show that oncogenic GRM3 variants dysregulate cAMP signaling, a heretofore unknown role for these oncogenes. cAMP signaling has been implicated in melanoma progression and drug resistance, and our data show that oncogenic properties of GRM3 could be mediated, at least in part, by alterations in cAMP signaling.